Board of Directors, Audit Committee, and Earnings Management - LIU, Tong (2017)
This study explores how the board of directors and audit committee affect earnings management by analyzing FTSE 100 companies during 2011-2016. The board independence, the board leadership structure, the board size, and the frequency of board meeting are considered as board characteristics. As shown in regression results, the board with a high proportion of independent directors is less likely to involve in earnings management. There is a negative relation between the frequency of board meeting and discretionary accruals in this empirical test. In addition, the larger firm is related to less earnings management. However, no significant relations are found between the leadership structure and earnings management. As for the audit committee characteristics, the independence, the size, and the degree of activity are investigated. No significant effects of audit committee characteristics on earnings management are found in this study.